Thermal Propagation Test Bench for the Study of the Paschen Curve and Lightning Arcs of Venting Gas - Björn Mulder; Kai Peter Birke; Björn Obry; Stefan Wigger; Ruslan Kozakov; Pavel Smirnov; Jochen Schein (Batteries)
Thermal propagation events are characterized by fire and thick black smoke, leading to propagation methods with a focus on preventing heat transfer and optimizing gas flow. Yet little attention is being paid to the electric conductivity of the gas, leading to possibly unexpected battery casing openings due to lightning arcs as well as potentially providing the minimum ignition energy. This gas composition (omitting particles) was used at different temperatures and pressures in a lightning arc test bench, leading to the Paschen curve. Using a mini-module cell setup, filtered venting gas was flowed through another lightning arc test bench, allowing for in situ measurements.